A prospective multicenter international single-arm observational study on the oncological safety of the sentinel lymph node algorithm in stage I intermediate-risk endometrial cancer (SELECT, SEntinel Lymph node Endometrial Cancer Trial). Issue 10 (22nd July 2020) - Grassi, Tommaso; Mariani, Andrea; Cibula, David; Soliman, Pamela T; Suman, Vera J; Weaver, Amy L; Pedra Nobre, Silvana; Weigelt, Britta; Glaser, Gretchen E; Cappuccio, Serena; Abu-Rustum, Nadeem R
Abstract : Background: In the primary treatment of apparent uterine-confined endometrial carcinoma, pelvic ± para-aortic lymphadenectomy has been considered the standard of care. Although some retrospective data suggest that the sentinel lymph node algorithm without complete lymphadenectomy can be used without jeopardizing oncologic outcome, prospective data are lacking. Primary Objectives: To assess the 36 month incidence of pelvic/non-vaginal recurrence in women with pathologically confirmed stage I intermediate-risk endometrioid endometrial carcinoma who have bilateral negative pelvic sentinel lymph nodes. Study Hypothesis: We hypothesize that patients with stage I, intermediate-risk endometrioid endometrial carcinoma who have bilateral negative pelvic sentinel lymph nodes will demonstrate a pelvic/non-vaginal recurrence rate comparable to historical estimate of stage I, intermediate-risk endometrioid endometrial carcinoma patients (estimated 2.5%). Trial Design: This prospective multicenter single-arm observational study will follow women with stage I, intermediate risk endometrioid endometrial adenocarcinoma who have undergone successful hysterectomy, bilateral salpingo-oophorectomy, and bilateral sentinel lymph node biopsies, for recurrence. All patients will undergo lymphatic mapping using indocynanine green and will either receive no adjuvant treatment or vaginal brachytherapy only. Patients will be followed for 36 months. Major Inclusion/Exclusion Criteria: Patients will be enrolled in the study cohort if all the following criteria are met: (i) at time of surgery: hysterectomy with bilateral adnexectomy, and successful bilateral pelvic sentinel lymph node mapping; (ii) on final pathology: pathologic stage I, intermediate-risk endometrioid endometrial carcinoma (grade 1 or grade 2 with ≥50% myometrial invasion, or grade 3 with <50% myometrial invasion), negative pelvic peritoneal cytology, and bilateral sentinel lymph nodes negative for malignancy; (iii) recommended adjuvant treatment: vaginal brachytherapy or no adjuvant treatment. Primary Endpoint: Incidence of pelvic/non-vaginal recurrence at 36 months. Sample Size: 182 patients for study cohort Estimated Dates for Completing Accrual and Presenting Results: Accrual will be completed in 2023 with results reported in 2026. Trial Registration: NCT04291612